Relationship between actual evapo-transpiration and estimated evapo-transpiration of a reference crop of indian mustard (Brassica juncea) - SAVANI, M B; PATEL, E I; SHEKH, A M; CHINCHGHARE, R B; PARMER, R S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1990-92 to find out the actual evapo-transpiration and evapo-transpiration of a reference crop by different methods in indian mustard [Brassica juncea (L.) Czernj. & Casson]. Total evapo-transpiration values of lysimetric. Penman, pan evaporation and radiation methods were 365.1, 431.0. 432.9 and 481.9 mm respectively. The values of crop coefficient (kc) by the last 3 methods for the whole crop-growing season were 0.85. 0.84 and 0.75 respectively. The kc values during different phenopilascs were estimated by different methods. The maximum kc values were attained during flowering. pod-formation and grain-formation stages. The water-lise efficiency was 3.7 kg/ha-mm.